Cyber security threats and web vulnerability analysis of higher educational institutions in Bangladesh - Hasan Khan Janny, Shadiqul; Asadujjaman Noor, Md.; Enan Al Harun Sahan, Mohammad; Nafez Sadnan, Sheikh; Towfiqur Rahman, Muhammad; Saleh Md Bakibillah, Abu (Institute of Advanced Engineering and Science, 2025)
This paper presents a comprehensive analysis of cyber security threats and web vulnerabilities in the context of higher educational institutions in Bangladesh, including twenty public and private universities. Educational institutions are highly vulnerable due to their negligence in maintaining a functional network, mainly owing to budgetary constraints. As a result, they have become a hacker playground for many ambitious adversaries to boast their technical skills, regardless of the harm they may inflict. Through the use of vulnerability assessment and penetration testing (VAPT), we conducted a methodical analysis of the institutions’ web infrastructures, identify and categorize the prevalent security threats and vulnerabilities that may compromise the integrity, confidentiality, and availability of information systems. Our findings reveal significant disparities in the security strength of both public and private universities, with the latter demonstrating a higher degree of vulnerability due to varying factors, such as budget constraints, policy enforcement, and awareness levels. This study underscores the urgent need for robust cyber security frameworks tailored to the higher educational sector’s unique requirements, advocating for proactive measures to mitigate potential cyber threats. The implications of this research extend beyond the academic domain, offering insights into national cyber security strategies and the safeguarding of critical information infrastructures.